EKSISTENSI MAHARAH KALAM DALAM PEMBELAJARAN BAHASA ARAB KONTEMPORER DI LEMBAGA STUDI BAHASA ASING - M. Naufal Al Qurthuby Fuady S.; Halimi Zuhdy; Idrus Muchsin Bin Agil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the existence of maharah kalam (Arabic speaking skills) in contemporary Arabic language learning at the Foreign Language Study Institute of Jalaluddin Arrumi Dormitory, Nurul Jadid Islamic Boarding School. The research focuses on identifying teaching strategies, learning media, student motivation, and obstacles encountered in developing Arabic speaking skills in both traditional and contemporary contexts. This study employed a descriptive qualitative approach involving 30 students and 4 Arabic teachers selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using thematic analysis techniques. The findings reveal that maharah kalam remains an essential competency in contemporary Arabic learning despite challenges such as limited mastery of modern vocabulary, dialect differences, and lack of speaking practice outside the classroom. Teachers implemented adaptive strategies including repetitive speaking exercises, collaborative discussions, and interactive digital media, which significantly improved students’ speaking fluency, confidence, participation, and comprehension. In addition, students with strong intrinsic motivation and consistent independent practice demonstrated better communicative abilities and vocabulary mastery. The study concludes that the integration of traditional teaching methods with digital technology and contextual learning materials plays an important role in maintaining the relevance and sustainability of maharah kalam in contemporary Islamic boarding school education.